Implementing the Deep Learning Approach for Religious Literacy in Early Childhood: A Case Study - Risnawati, Atin; Hafidhoh, Husnul; Permadi, Muhammad (THUFULA, 2026)
Early childhood education provides a crucial foundation for character development, including the cultivation of religious literacy. Within the context of the Merdeka Curriculum, which offers flexibility for early childhood education institutions, the Deep Learning approach has emerged as a promising strategy for fostering the holistic internalization of Islamic values. This study aimed to examine the implementation of the Deep Learning approach in fostering religious literacy among young children at IT Syntax Bubbly School Kindergarten. Employing a qualitative case study design, data were collected through participatory observations, in-depth interviews, and document analysis involving purposively selected teachers, the principal, and students. Data were analyzed using the Miles and Huberman interactive model. The findings revealed that the Deep Learning approach was implemented through exploratory, reflective, and project-based strategies, which supported children's understanding, appreciation, and enactment of religious values. The integration of religious literacy into daily activities, along with collaboration with parents, further facilitated the internalization of these values. However, several challenges were identified, including limited learning media and insufficient teacher competence. The study highlights the potential of the Deep Learning approach to support the holistic development of religious literacy in early childhood. It underscores the importance of strengthening teacher capacity and learning resources to optimize its implementation.